The Pripree Model of Bantumsue Community to Nawatwithi (Local Innovative) for Industries Handicrafts Design with Enhancing Participation Action Approach - Wongsuwan, Surapa; Khiaomang, Kriangsak; Seo, Miyung (Journal of Community Development Research (Humanities and Social Sciences); Vol 15 No 1 (2022): January - March 2022DO - 10.14456/jcdr-hs.2022.4, 2022)
The objectives of this research were 1) to synthesize the design development of industrial handicraft prototype of Bantumsue community; and 2) to evaluate the product design of industrial handicraft to produce the product manuals for community. An agricultural leftover’s experiment was established where design A is a product from banana cladding materials, design B is bamboo leaf and design C is pineapple. Data were collected using questionnaire and in-dept interview form and analyzed using the formula of Trixie Blend Diagram, percentage and mean. The 175 samples for the research consisted of experts, tourists and designers to evaluate the design, the environmental impact and graphic design of the prototype of handicraft.           The research revealed that 1) Selecting materials with the least environmental impact showed the highest level of satisfaction with the average value of 4.46 (SD = 0.67); 2) The average of material consumption was 4.38 (SD = 0.63); which is similar to 3) The appropriated manufacturing processes, which was 4.38 (SD = 0.63); 4) The average value of reducing environmental impact was 4.37 (SD = 0.68); 5) Suitable service life showed the average value as 4.12 (SD = 0.72); 6) The prototype of industrial handicrafts design showed a high level of satisfaction with the average value of 4.44 (SD = 0.61); and 7) Proper end-of-life management system was at moderate level with the average value of 4.37 (SD = 0.73). According to the 123 participants or 26.15% agreed that the processing of waste from fiber paper could create the most appropriate handicraft. In addition, 1) The product design B (from bamboo leaf) showed the most satisfied creative handicraft with the average value of 4.58 (SD = 0.56); 2) The graphic design of handicraft prototype no. 11 and 09 highlighted the most satisfied with the mean of 4.33 (SD = 0.73); and 3) The logo design of layout no. 6 was the highest level of satisfaction with the mean of 4.20 (SD = 0.90). Keywords: Bantumsue Community, Industries Handicrafts Design, Community Participation